2014
DOI: 10.1038/nutd.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding and metabolic syndromes: two sides of the same coin

Abstract: Refeeding syndrome describes the metabolic and clinical changes attributed to aggressive rehabilitation of malnourished subjects. The metabolic changes of refeeding are related to hypophosphatemia, hypokalemia, hypomagnesemia, sodium retention and hyperglycemia, and these are believed to be mainly the result of increased insulin secretion following high carbohydrate intake. In the past few decades, increased consumption of processed food (refined cereals, oils, sugar and sweeteners, and so on) lowered the inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 82 publications
(122 reference statements)
2
17
0
7
Order By: Relevance
“…Increased insulin resistance associated with RFS, also observed in our population, could add to the risk of infection and sepsis [27]. Mechanisms of hyperglycemia and hyperinsulinemia, compatible with an increased insulin resistance among RFS patients have been well described in an article of Obeid et al [28].…”
Section: Subgroup Analysis: Hypocaloric Vs Normocaloric Intakesupporting
confidence: 63%
“…Increased insulin resistance associated with RFS, also observed in our population, could add to the risk of infection and sepsis [27]. Mechanisms of hyperglycemia and hyperinsulinemia, compatible with an increased insulin resistance among RFS patients have been well described in an article of Obeid et al [28].…”
Section: Subgroup Analysis: Hypocaloric Vs Normocaloric Intakesupporting
confidence: 63%
“…During starvation, intracellular potassium is depleted, while its serum concentration may remain normal. Upon refeeding, potassium enters into cells because of insulin secretion and consequently the serum concentration of this mineral reduces (Mehanna 2008, Obeid et al 2014. In the present study, the potassium level also decreased during refeeding and the serum sodium and potassium levels changed in a relatively opposite manner, which can be associated with Na-K ATPase symporter action.…”
Section: Discussionmentioning
confidence: 49%
“…Following feeding, low serum phosphate concentration is related to increased blood glucose level and decreased insulin sensitivity (Friedman 2007). Decline in the serum phosphate concentration can take place as a result of insulin secretion (Obeid et al 2014). In refeeding syndrome, total body phosphate depletion occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the starvation status, the body shifts from carbohydrate to fat and protein utilization to produce glucose and energy. In the refeeding status, the body shifts back instantaneously to carbohydrate metabolism [2][3][4]. Studies on anorexia nervosa patients and fish species showed that the starvation period has prooxidant effects due to both increased lipid peroxidation levels and the reduced level of antioxidant defenses [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%